THE EFFECT OF INSTAGRAM IN LEARNING ENGLISH VOCABULARY - alfu; Nur Asmawati; Fitriningsih; Nurdin (Datokarama English Education Journal, 2021)
The aims of this research are to find out the effect of Instagram in learning vocabulary of third semester students at English Tadris Study Program in IAIN Palu. This research was quantitative method and used total sampling. The subject of this research was the students’ batch 2019 semester 3 academic year 2020-2021 in IAIN Palu. The total numbers of students of in this research were 102 students. After selected the sample of this research were 35 students. Research instrument is questionnaire.The technique of collection data was observation, and reduction.The result showed that Effect of Instagram in Learning Vocabulary of Third Semester Students’ at English Tadris Study Program in IAIN Palu Academic year 2020/2021, used online media namely google form. The data revealed that the level of the mean score 62,48% from 35 students which was categorized as high effect. Then the research concluded that it is evident that Instagram have an effect on learning English (vocabulary) of student. It was revealed by the mean score 62,48%. The research was classified as high category of the students’ questionnaire.